Implementation of Digital Marketing to Increase Sales Volume (Study at DW Sport Store) - Muhammad Rezky, Reza; Anggi Josetiyo Prayoga (Journal of Managiere and Business, 2024)
This research explores the implementation of digital marketing strategies to increase sales volume at DW Sport stores. In the digital era, consumer behavior has experienced a significant shift. More and more people are looking for products and services via the internet, social media and other online platforms . Therefore, this study aims to identify key steps that can help DW Sport stores effectively utilize the potential of digital marketing. The study covers various elements of digital marketing, including creating responsive, search engine-optimized websites, using social media to build relationships with customers, using email marketing to communicate with audiences, paid advertising campaigns to increase visibility, and data analysis to understand performance. campaign. The research results show that the implementation of digital marketing strategies has had a positive impact on the sales volume of DW Sport stores. Through the use of social media, email marketing, and paid advertising campaigns, the store has been able to reach and interact with a wider audience. Data analysis helps in better decision making and real-time campaign adjustments. These findings  underscore  the  importance  of  investing  in  resources  and knowledge to implement digital marketing successfully DW Sport stores and  similar  businesses  can  take  advantage  of  these  steps  to  remain  competitive in  an increasingly digital marketing environment. This research provides valuable insight into how digital marketing can be an effective tool for increasing sales volume in physical stores. Penelitian ini mengeksplorasi penerapan strategi pemasaran digital untuk meningkatkan volume penjualan di toko DW Sport. Di era digital, perilaku konsumen mengalami perubahan yang signifikan. Semakin banyak orang yang mencari produk dan jasa melalui internet, media sosial dan platform online lainnya. Oleh karena itu, penelitian ini bertujuan untuk mengidentifikasi langkah-langkah penting yang dapat membantu toko DW Sport memanfaatkan potensi pemasaran digital secara efektif. Studi ini mencakup berbagai elemen pemasaran digital, termasuk pembuatan situs web yang responsif dan dioptimalkan mesin pencari, penggunaan media sosial untuk membangun hubungan dengan pelanggan, penggunaan pemasaran email untuk berkomunikasi dengan audiens, kampanye iklan berbayar untuk meningkatkan visibilitas, dan analisis data untuk memahami kinerja. kampanye. Hasil penelitian menunjukkan bahwa penerapan strategi pemasaran digital memberikan dampak positif terhadap volume penjualan toko DW Sport. Melalui penggunaan media sosial, pemasaran email, dan kampanye iklan berbayar, toko telah mampu menjangkau dan berinteraksi dengan khalayak yang lebih luas. Analisis data membantu pengambilan keputusan yang lebih baik dan penyesuaian kampanye secara real-time. Temuan ini menggarisbawahi pentingnya investasi pada sumber daya dan pengetahuan untuk menerapkan pemasaran digital dengan sukses. Toko DW Sport dan bisnis serupa dapat memanfaatkan langkah-langkah ini untuk tetap kompetitif dalam lingkungan pemasaran digital yang semakin meningkat. Penelitian ini memberikan wawasan berharga tentang bagaimana pemasaran digital dapat menjadi alat yang efektif untuk meningkatkan volume penjualan di toko fisik.